Genetic detection and phenotypic detection of the mutant S3RB gene using mutagens by radioactive sources, lasers and magnetic water encoded into mutant pyocin produced from mutant Pseudomonas aeruginosa - Mohammed, Nebras Rada (International Journal of Aquatic Research and Environmental Studies, 2026)
Objective: The aim of this research is a genetic and phenotypic study of the mutant S3RB gene encoded to pyocin (bacteriocin) from mutant Pseudomonas aeruginosa after exposure to physical mutagens. Study design: Cross-sectional in descriptive and case–control in analytical study design. Backgrounds: P. aeruginosa is gram negative bacteria, a multi-drug resistance (MDR), profiteer pathogen occasion several diseases acute, chronic contagion in immunodeficiency patients to chronic obstructive pulmonary disease (COPD), cystic fibrosis, cancer, sepsis, burns, traumas and COVID-19. Utmost strains production bacteriocin able of prohibit another strains known pyocin that are classified to kinds inclusive R- type, F-type, S-type and others. Results: Results of phenotypic detection of mutant pyocin for (16) isolates of mutant P. aeruginosa after mutagenesis Methodology: Study patients, bacterial strain, media and growth conditions of Pseudomonas aeruginosa. Exposure to physical mutagenesis by physical mutagens. Phenotypic of pyocin (bacteriocin) before and after mutagenesis. Genotypic detection of pyocin (bacteriocin) before and after mutagenesis by PCR device. through formation large inhibition zone against Staphylococcus aureus around the hole (contain P. aeruginosa). In molecular genetics results of genotypic detection by PCR of pyocin produced from P. aeruginosa include positive results with two band size of product of S3RB (451 with 600) bp. in No. 1, 7, 8, 10, 11, 17, 19, 20 and 21. Also, positive results of one band for the same gene (451) bp. in No. 2, 3, 5, 9, 15 and 16, but negative results in No.4, 6, 12, 13, 14, 18, 22 and 23. Conclusion: Cs137, Co60, Na23 and Sr90 radioactive sources without aluminum led to a mutation in the S3RB gene encoding pyocin in P. aeruginosa. Innuendo to radiation released of a Cs137 irradiant exporter in the presence of aluminum led to a mutation. The best physical mutagen for the S3RB gene is radiation emitted from radioactive sources.